INDICATION, PREVALENCE AND MATERNAL OUTCOME OF EMERGENCY PERIPARTUM HYSTERECTOMY: A CROSS-SECTIONAL STUDY. - Nikhat Fatma (Student's Journal of Health Research Africa, 2024)
Background Emergency peripartum hysterectomy (EPH) is a critical surgical procedure performed to control life-threatening postpartum hemorrhage (PPH) when conservative measures fail. The study aims to assess the frequency, indications, and maternal outcomes of EPH. Methods A total of 144 women who underwent EPH following failed conservative management for PPH were included. Data were collected on maternal demographics, indications for hysterectomy, type of hysterectomy performed, and post-operative complications. Statistical analysis was accomplished using SPSS version 23.0. Results The average age of the patients was 29.5 ± 4.3 years, with 61.1% being multiparous. Previous cesarean sections were documented in 38.9% of cases. The leading indication for EPH was uterine atony (45.8%), followed by placenta previa (22.2%), placenta accreta (18.8%), and uterine rupture (13.2%). Total hysterectomy was performed in 72.9% of cases, while 27.1% underwent subtotal hysterectomy. Immediate postoperative complications occurred in 52.1% of patients, with infections (22.2%) and hemorrhage requiring additional surgery (16.7%) being the most common. A significant association was found between previous cesarean sections and the incidence of placenta accreta (χ²=12.34, p=0.002), as well as between total hysterectomy and higher postoperative complications (p=0.045). Conclusion Uterine atony and abnormal placentation are the predominant indications for EPH in this setting, with a substantial burden of postoperative complications observed. Prior cesarean deliveries significantly increase the risk of placenta accreta, underscoring the need for cautious evaluation of cesarean indications. Recommendations Enhancing antenatal care with early identification and management of high-risk pregnancies, promoting skilled birth attendance, and implementing standardized protocols for PPH management can potentially reduce the incidence of EPH and improve maternal outcomes. Additionally, efforts to limit unnecessary primary cesarean sections could decrease the risk of abnormal placentation in subsequent pregnancies.